The rights and obligations of consumers, banks and developers in the home purchase agreement through the home ownership loan facility (STUDY PT.PILAR WAHANA SEJATI) - Ahadin, Ahadin; Azmi, Syariful; Sahputra, Rilawadi (Universitas Dharmawangsa, 2024)
This study aims to (1) Examine and analyze the legal relationship between consumers and developers due to the Home Purchase Agreement. (2) reviewing and analyzing the legal protection of Home consumers due to the obligations of the developer due to the house sale and purchase agreement. The research method used is juridical normative by using conceptual (conceptual approach). Data analysis is done qualitatively by utilizing relevant positive theories and laws. Legal protection of consumers is regulated in law No. 8 of 1999 on consumer protection this law is expected to protect consumers in buying and selling homes through home ownership credit facilities. Based on the rules of law ,then in making the sale and purchase of houses must be made in the form of an authentic deed that is a deed that is made in the form specified by law and made before the competent public officials. Deed of sale and purchase under Article 617 of the Civil Code Kepmenpera number 09/1995 and PP24 / 1997, The Deed of sale and purchase must be signed by the seller and buyer in the presence of PPAT.